Characterization of the roles of amphiregulin and transforming growth factor β1 in microvasculature-like formation in human granulosa-lutein cells - Li, Hui; Chang, Hsun-Ming; Li, Saijiao; Klausen, Christian; Shi, Zhendan; Leung, Peter C.K. (Frontiers in Cell and Developmental Biology, 2022)
Vascular endothelial-cadherin (VE-cadherin) is an essential component that plays a regulatory role in angiogenesis during the process of corpus luteum formation. Amphiregulin (AREG) and transforming growth factor β1 (TGF-β1) are two intrafollicular factors that play opposite roles in regulating luteinization and progesterone production in human granulosa-lutein (hGL) cells. Whether AREG or TGF-β1 regulates the expression of VE-cadherin and subsequent angiogenesis in the human corpus luteum remains to be elucidated. We demonstrated that hGL cells cultured on Matrigel can spontaneously form two typical endothelial cell phenotypes, capillary-like and sprout-like microvascular patterns. Using a dual inhibition approach (small molecular inhibitors and siRNA-based knockdown), our results showed that AREG promotes microvasculature-like formation in hGL cells by upregulating the expression of VE-cadherin. However, TGF-β1 suppresses microvasculature-like formation in hGL cells by downregulating the expression of VE-cadherin. Additionally, the AREG-induced upregulation of VE-cadherin is mediated by the EGFR-ERK1/2 signaling pathway, while the TGF-β1-induced downregulation of VE-cadherin is mediated by the ALK5-SMAD2/3/4 signaling pathway. Our findings provide important insights into the underlying molecular mechanisms by which two intrafollicular growth factors differentially regulate the formation of the corpus luteum in human ovaries.